Finite element computational dynamics of rotating systems, an addendum (A bibliography (1998-2004)) - Mackerle, Jaroslav (Computer Assisted Methods in Engineering and Science, 2006)
Gives a bibliographical review of the finite element analyses of rotating systems from the theoretical as well as practical points of view. The bibliography lists references to papers, conference proceedings and theses/ dissertations that were published between 1998- 2004. It is a continuation of the author's earlier bibliography with the same title published in Shock Vibration 6 (1999) 209-222 where papers published between 1994-1998 are listed. At the end of this paper 479 references are listed.